Rações contendo antioxidantes extraídos da fauna acompanhante de camarões marinhos: Efeitos sobre a fisiologia do camarão-da-Malásia (Macrobrachium rosenbergii) - Siqueira, Ana Carolina Louzã [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The shrimp Macrobrachium rosenbergii is the main freshwater shrimp farmed in Brazil and in several other countries. It has ease of management, adaptation to environmental conditions and good acceptance to different diets, being considered a good model for studies aiming the incorporation of feed additives. Our objective was to investigate the physiological effects of adding protein hydrolysates with antioxidant potential in the diet of M. rosenbergii. The hydrolysates were extracted from animals that constitute the accompanying fauna of the marine shrimp fishery in the state of São Paulo and that are discarded at sea. The animals were fed for 30 days on a control diet (without hydrolysates) or on a diet containing 10% hydrolysate. All diets were isocaloric and isopreoteic. A mesh of physiological processes were evaluated: ingestion, defecation and growth rates, metabolism, nitrogen excretion, feed conversion, hepatosomatic index (HSI) and type of energy substrate oxidized. Animals fed with feed containing 10% protein hydrolysates showed higher 5% intake rate and lower defecation rate 3.012 ± 0.239 (mg MS dayˉˡ), suggesting good feed utilization and greater environmental sustainability due to lower feces release rate into the culture medium and effluent. In addition, the group fed feed containing hydrolysates showed higher oxygen consumption rate and nitrogen excretion. However, these physiological responses were not accompanied by a higher growth rate, as the control animals (18%) grew more than the animals fed the feed containing hydrolysates (13%). The feed conversion ratio (FRC) was better in animals fed control feed (6.403 ± 0.613). It is possible that the introduction of the 10% concentration of hydrolysates to the diet was high and affected the absorption of some nutrients, metabolization, excretion and associated energetics. On the other hand, although a higher growth rate is an expected biological response in species of economic interest, other factors such as health, immunity, and reproduction must also be considered. During my Masters work I will evaluate other concentrations of the hydrolysates in the feed for M. rosenberguii and also the resilience of the species to different environmental stressors when fed with such additive.

O camarão Macrobrachium rosenbergii é o principal camarão de água doce cultivado no Brasil e em vários outros países. Ele possui facilidade de manejo, adaptação a condições ambientais e boa aceitação a diferentes dietas, sendo considerado um bom modelo para estudos que visam a incorporação de aditivos na ração. Nosso objetivo foi investigar os efeitos fisiológicos da adição de hidrolisados proteicos com potencial antioxidante na dieta de M. rosenbergii. Os hidrolisados foram extraídos de animais que constituem a fauna acompanhante da pesca de camarões marinhos no estado de São Paulo e que são descartados no mar. Os animais foram alimentados durante 30 dias com ração controle (sem hidrolisados) ou com ração contendo 10% de hidrolisado. Todas as dietas foram isocalóricas e isopreoteicas. Foi avaliada uma malha de processos fisiológicos: taxas de ingestão, defecação e crescimento, metabolismo, excreção nitrogenada, conversão alimentar, índice hepatossomático (HSI) e tipo de substrato energético oxidado. Animais alimentados com ração contendo 10% de hidrolisados proteicos apresentaram maior taxa de ingestão 5% e menor taxa de defecção 3,012 ± 0,239 (mg MS diaˉˡ), sugerindo um bom aproveitamento do alimento e maior sustentabilidade ambiental devido a menor taxa de liberação de fezes no meio de cultivo e efluente. Além disso, o grupo alimentado com ração contendo hidrolisados apresentou maior taxa de consumo de oxigênio e excreção nitrogenada. No entanto, essas respostas fisiológicas não foram acompanhadas de maior taxa de crescimento, uma vez que os animais controles (18%) cresceram mais que os animais alimentados com ração contendo hidrolisados (13%). A taxa de conversão alimentar (FRC) foi melhor nos animais alimentados com ração controle (6,403 ± 0,613). É possível que a introdução da concentração de 10% de hidrolisados à dieta tenha sido elevada e afetado a absorção de alguns nutrientes, metabolização, excreção e energética associada. Por outro lado, embora uma maior taxa de crescimento seja uma resposta biológica esperada em espécies de interesse econômico, outros fatores como saúde, imunidade e reprodução também devem ser considerados. Durante o meu trabalho de mestrado irei avaliar outras concentrações dos hidrolisados na ração para M. rosenbergii e também a resiliência da espécie à diferentes estressores ambientais quando alimentada com tal aditivo.
Feeds containing antioxidants extracted from the bycatch of marine shrimp: Effects on the physiology of the Malaysian shrimp (Macrobrachium rosenbergii)
Keywords: Hidrolisado proteico; Fauna acompanhante; Ração; Camarão da Malásia; Camarão Criação